The Failure of the Afghan Peace Process and the Fall of Kabul: Implications for Afghanistan and Pakistan - Asifa Jahangir; Zafar Iqbal Yousafzai; Ahmad Saleem (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Unintended consequences in international relations may be tracked in three ways: Irrational policies that harm a state’s interests owing to diplomatic brinkmanship. Second, tense relationships (spiraling out of control) have their own logic regardless of the best interests of those involved. Third, the outcome was unanticipated or against one’s self-interests. By evacuating American and NATO troops from Afghanistan, the Taliban escalated their activities, resulting in Kabul’s collapse. Obama fought Taliban fighters through military operations and drone strikes. The Afghan peace process, which failed and led to the withdrawal of American-led NATO troops under Biden, shows that this Afghan territory is a "graveyard of empires." This brinkmanship game has had little effect on the sole superpower and its allies, but Afghanistan and Pakistan may suffer from unanticipated consequences. This article concerns the Afghan peace process, Pakistan’s role, and post-Taliban Afghanistan. Similarly, it examines the unintended consequences of the Afghan peace process’s failure and Kabul’s fall to the Taliban for Afghanistan and Pakistan. Using qualitative research interviews, this article explores Pakistan’s various action options in Afghanistan.